2018
DOI: 10.1007/s11010-018-3413-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular changes to the rat renal cotransporters PEPT1 and PEPT2 due to ageing

Abstract: Renal PEPT1 and PEPT2 cotransporters play an important role in the balance of circulating body oligopeptides and selected peptidomimetic drugs. We aim to comprehensively characterise age-related changes of the renal PEPT cotransporters at the gene, protein, and functional level. Brush border membrane vesicles (BBMV) and outer medulla membrane vesicles (OMMV) were isolated from the kidneys of young, middle-aged and old rats. The protein expression of PEPT1 was not only increased in BBMV from old rats, but PEPT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…A monotonic increase in PepT2 was observed in the expression from fetal d20 to d75 (adult) and was more pronounced in older groups [ 114 ]. This is consistent with Alghamdi et al (2019) who identified that PepT2 was regulated by aging and that the expression of PepT2 in the kidney of aged rats was increased compared with both young adult and middle-aged rats, but no remarkable changes were observed between these two groups [ 113 ]. The expression of mouse PepT2 in the prostate was increased during development and remained at a plateau level after sexual maturation [ 38 ].…”
Section: Regulation Of Pept2supporting
confidence: 91%
See 1 more Smart Citation
“…A monotonic increase in PepT2 was observed in the expression from fetal d20 to d75 (adult) and was more pronounced in older groups [ 114 ]. This is consistent with Alghamdi et al (2019) who identified that PepT2 was regulated by aging and that the expression of PepT2 in the kidney of aged rats was increased compared with both young adult and middle-aged rats, but no remarkable changes were observed between these two groups [ 113 ]. The expression of mouse PepT2 in the prostate was increased during development and remained at a plateau level after sexual maturation [ 38 ].…”
Section: Regulation Of Pept2supporting
confidence: 91%
“…In the heart, PepT2 expression in Wistar rats was regulated by aging [ 113 ]. The expression of PepT2 in the hearts of middle-aged and old Wistar rats was significantly upregulated compared with that in the young adult group.…”
Section: Regulation Of Pept2mentioning
confidence: 99%
“…The expression of PepT1 is dysregulated in diabetes [44,[73][74][75]. Studies conducted in rodents have suggested that the tissue distribution, protein expression and/or transport activity of PepT1 and PepT2 may be altered due to aging and hypertension [64,76,77]. These findings have suggested that nutrient regulation and drug response (e.g., to ACE inhibitors) may be altered in populations with underlying medical conditions.…”
Section: Regulation Of Pept1 and Pept2 In Diseasementioning
confidence: 99%
“… As well as activating melatonin receptors (MTRs), MT1R and MT2R, pineal and local, exogenous melatonin may also be directly taken up into mitochondria by the peptide transporter 1/2 (PEPT1/2), whilst the sulphation metabolites of melatonin can be taken into mitochondria by the organic anion transporter 3 (OAT3) [ 191 ]. Factors acting to regulate PEPT1/2 and OAT3 provide other aspects of how melatonin regulates the plasticity of cellular and mitochondrial responses, such as the suppression of PEPT1/2 over aging [ 192 ]. How relevant is the direct uptake of pineal and local melatonin into mitochondria in the cells of the tumor microenvironment?…”
Section: Future Research Implicationsmentioning
confidence: 99%